Measuring Villagers’ Satisfaction about Performance of Village Government at Shemiranat in Large Lavasan: a Scope for the Use of Models - Homay Salehi, Khadijeh; Heydari, Abolfazle (International Journal of Bio-resource and Stress Management, 2023)
Today due to complexity of problems and requirement and necessity of availability to development, we need professional organization in local management such as rural governments. Each service organization needs evaluation of programs and activities assessment in deciding best policy and modifying procedures and existing programs. Rural government is the main organization of rural management has influential effect in providing public services and organizing rural life. Their satisfaction of the people may be based on scientific methods. This preliminary study measures the satisfaction of villagers in large Lavasan village about performance of rural government using models such as Teboul method, Lacking of expectation realization model, Nour Yakey Kano model, American Customer Satisfaction Index Model (ACSI), Servqual model, Researcher’s suggestive model. Ninety households were randomly selected as sample and questionnaires were distributed among them. Preliminary information was noted based on the survey.